A study of single minute exchange of die methodology improvement using design-based elements - Amirul Hakimi Md Yusoff (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The main goal of this research, besides analyzing the work of Shingo (1985), which is generally acknowledged as a "reference" book for a changeover method, is as follows; to devise a new 'SMED' methodology by applying design-centric improvement, such as Design for assembly (DFA) principles; to implement the new methodology on a preexisting case study as a method of comparison between the original and new methodology; to quantify the improvements made by the alternative method using OEE (Overall Equipment Effectiveness) method to validate the devised methodology and prove the value of design in 'SMED' methodology.